2001
DOI: 10.1177/021849230100900313
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Giant Coronary Artery Aneurysm

Abstract: A 39-year-old man and a 38-year-old woman were diagnosed to have giant coronary artery aneurysm with a fistula to the left ventricle. Coincidental aortic valve incompetence was also present in the man. The manifestations and successful surgical management of this rare pathology are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Some authors argue that CAA of at least three to four times the size of the original vessel diameter is an absolute indication for surgical intervention because of the propensity for complications such as compression, rupture, or thrombosis. 8 In our case the patient was symptomatic, complicated with CAF, and in danger of rupturing if left untreated. When a giant CAA is very large, axillar, or femoral artery cannulation for cardiopulmonary bypass may be necessary to relieve the compression of ventricle inflow tract for the resection of giant aneurysm, 15 like it was in In our case.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Some authors argue that CAA of at least three to four times the size of the original vessel diameter is an absolute indication for surgical intervention because of the propensity for complications such as compression, rupture, or thrombosis. 8 In our case the patient was symptomatic, complicated with CAF, and in danger of rupturing if left untreated. When a giant CAA is very large, axillar, or femoral artery cannulation for cardiopulmonary bypass may be necessary to relieve the compression of ventricle inflow tract for the resection of giant aneurysm, 15 like it was in In our case.…”
Section: Discussionmentioning
confidence: 62%
“…Coronary artery aneurysms are an uncommon condition, although there has been an increase in their diagnoses since the current cardiac diagnostic imaging has improved. Giant CAAs are rarely seen, 8 and their main causes include atherosclerosis, Kawasaki disease, complications of percutaneous transluminal coronary angioplasty, and endocarditis. 4 …”
Section: Discussionmentioning
confidence: 99%
“…It is a rare entity that the giant CAA combined with coronary artery fistula. Yu et al [4] reported that CAA was found in 5.9 % of patients with congenital coronary artery fistula, which was found in only 0.2 % of patients who had undergone open heart surgery. To the giant aneurysm, which arose form the left main trunk and located in the atrial septum, there has never been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%